2006
DOI: 10.1073/pnas.0506643103
|View full text |Cite
|
Sign up to set email alerts
|

The ratToxo1locus directs toxoplasmosis outcome and controls parasite proliferation and spreading by macrophage-dependent mechanisms

Abstract: Toxoplasmosis is a healthcare problem in pregnant women and immunocompromised patients. Like humans, rats usually develop a subclinical chronic infection. LEW rats exhibit total resistance to Toxoplasma gondii infection, which is expressed in a dominant mode. A genome-wide search carried out in a cohort of F 2 progeny of susceptible BN and resistant LEW rats led to identify on chromosome 10 a major locus of control, which we called Toxo1. Using reciprocal BN and LEW lines congenic for chromosome 10 genomic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 37 publications
6
72
0
7
Order By: Relevance
“…Different host species are more or less susceptible. The genetic background of a given species, as demonstrated for different mouse or rat strains, may also influence the expression of virulence (51).…”
Section: Genotypes and Virulencementioning
confidence: 99%
“…Different host species are more or less susceptible. The genetic background of a given species, as demonstrated for different mouse or rat strains, may also influence the expression of virulence (51).…”
Section: Genotypes and Virulencementioning
confidence: 99%
“…Reciprocal LEW ϫ BN lines congenic for Toxo1 have allowed for the mapping of the genes responsible for the robust resistance phenotype to a region on rat chromosome 10 (4). These studies further demonstrated the central role played by macrophages in the immune defense against T. gondii, known for humans (5) and clearly seen in rat macrophages (3,4).…”
mentioning
confidence: 84%
“…Recently, a region of the rat genome, named Toxo1, has been shown to be associated with resistance to T. gondii (3,4). Compared to rats of the susceptible Brown Norway (BN) strain, LEW (Lewis) strain rats are extremely resistant to T. gondii infection: few to no parasites are found postinoculation, very few encysted bradyzoites are found, no antibody is produced, and there is no transmission to their pups.…”
mentioning
confidence: 99%
“…In some cases, both the host and the parasite die when an animal host is infected with the RH strain. For example, mice will die very quickly when they are infected with the RH strain without any treatment whereas rats can survive without any observed clinical signs because the RH strain is unable to grow in these animals due to innate immunity (77)(78)(79).…”
Section: Brucei)mentioning
confidence: 99%